2009
DOI: 10.1016/j.chembiol.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Reverse and Chemical Genetic Screens Reveals Angiogenesis Inhibitors and Targets

Abstract: SUMMARY We combined reverse and chemical genetics to identify targets and compounds modulating blood vessel development. Through transcript profiling in mice, we identified 150 potentially druggable microvessel-enriched gene products. Orthologs of 50 of these were knocked down in a reverse genetic screen in zebrafish, demonstrating that 16 were necessary for developmental angiogenesis. In parallel, 1280 pharmacologically active compounds were screened in a human cell-based assay, identifying 28 compounds selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 49 publications
(51 reference statements)
4
37
0
Order By: Relevance
“…Now, knowing that the expression pattern of Paladin is abundant in the vasculature in late embryogenesis and adulthood, one could speculate that one additional function of Paladin is to regulate insulin signaling in the vasculature. Furthermore, we have previously shown that, in the zebrafish, Paladin is essential for normal vascular development and vascular perfusion (Kalen et al, 2009). Therefore, it is possible that Paladin has a broader role in regulating receptor tyrosine kinase and AKT phosphorylation in the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Now, knowing that the expression pattern of Paladin is abundant in the vasculature in late embryogenesis and adulthood, one could speculate that one additional function of Paladin is to regulate insulin signaling in the vasculature. Furthermore, we have previously shown that, in the zebrafish, Paladin is essential for normal vascular development and vascular perfusion (Kalen et al, 2009). Therefore, it is possible that Paladin has a broader role in regulating receptor tyrosine kinase and AKT phosphorylation in the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, statin use was found to be associated with a reduced risk of prostate (40) and colorectal cancer (41). Statins have recently been found to inhibit HUVEC proliferation (16), spheroid sprouting (19) and intersegmental vessel growth in zebrafish embryos (29). In contrast to angiogenesis, the effect of statins on lymphangiogenesis and lymphangiogenic sprouting had not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies were performed based on in vitro compound screens with blood vascular endothelial cells, including proliferation assays of human umbilical vein endothelial cells (HUVEC) (16), HUVEC/vascular smooth muscle cell cocultures, human microvascular endothelial cell tube formation assays (17,18), and HUVEC spheroid sprouting assays (19). While the tube formation assay has been considered as a model of vasculogenesis rather than angiogenesis (20), the other assays attempt to measure different aspects of blood vessel formation.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of recent studies have taken advantage of the optical clarity of zebrafish embryos and larvae to carry out live imaging of tubulogenesis in developing vessels within living animals (Ellertsdottir et al, 2010;Herbert and Stainier, 2011;Herwig et al, 2011;Jin et al, 2005Jin et al, , 2007Kalen et al, 2009;Kamei et al, 2006;Lenard et al, 2013;Wang et al, 2010). These studies have provided in vivo evidence substantiating both the cell hollowing and the cord hollowing models for lumenogenesis.…”
Section: Introductionmentioning
confidence: 96%